A new approach in the cost estimation of a hydroelectric power plants in Turkiye based on geographical features - Celikdemir, Soner; Ozdemir, Mahmut Temel (Wiley, 2022)
In this study, a new geographically based equation models with four terms and seven parameters are proposed for the total cost estimation of Hydroelectric Power Plants (HEPP). For this purpose, 25 basins in Turkiye are grouped into eight parts considering the similarities of their precipitation and elevation characteristics. For each group, the equation's parameters which is used to predict the cost of HEPPs, are determined by using the data of 67 HEPPs constructed over the last 6 years. In the literature, for the first time, the geographical characteristics of the regions in which HEPPS are constructed, were also considered in determining of the equation's parameters used to estimate the total cost of HEPPs. Chaos Embedded Adaptive Particle Swarm Optimization (CEAPSO) algorithm, which has a good performance in such problems is used. The obtained results are compared with the literature and the effectiveness of the proposed approach has been demonstrated. Finally, the sensitivity analyzes of the developed equation models are performed and the effects of power, head, and flow on HEPPs' total cost are illustrated.
Keywords: chaos embedded adaptive particle swarm optimization; geographical based cost estimation; hydroelectric power plant